MANAJEMEN PERENCANAAN KURIKULUM - Faishal (el Hakim Press, 2023)
The curriculum is a blue print of an educational institution, through the curriculum prospective guardians and prospective students can see what kind of competency picture will be obtained by their children or personal students. So that in planning the curriculum, managers of educational institutions should understand what they must prepare in planning a curriculum. Therefore, through library research or also called this literature study, the author collects library data, reads, records and processes from various sources, the main data sources are from books and journals that discuss the curriculum and are supported by the author's personal experience in the field in developing the curriculum to provide an objective picture of curriculum planning management.